Integrating affective responses into game theory: A dual selves model - Matthias Greiff (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
This paper develops a method to integrate affective reponses into game theoretical models. We illustrate our method in a team production framework. The model analyzes how concave and convex status preferences for esteem solve the problem of team production under complete and incomplete information about workers' abilities. Using a dual selves model, we model the choice of effort as a deliberative decision and the expression of esteem as an affective response. Modeling an individual's affective system as a seperate player allows us to apply standard game-theoretic solution concepts to analyze affective responses.
Keywords: D03; D21; D8; M5; 330